2012
DOI: 10.1002/sia.4920
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/carbon nanotube composite films electrosynthesis through diazonium salts electroreduction and electrochemical polymerization

Abstract: In this work, we combine two widely used techniques to produce modified electrodes, that is, the electroreduction of diazonium salts and the electropolymerization of conductive polymers in order to obtain polyaniline (PANI)/carbon nanotube (CNTs) composites. Thus, in a first step, a CNTs electrode was functionalized with 4-nitrophenyl group by electrochemical reduction of 4-nitrobenzenediazonium salt in nonaqueous media. Then, the nitro group was reduced electrochemically to amine functionality. Cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
6
11
0
Order By: Relevance
“…CNT/PANI nanocomposites prepared via in situ polymerization methods demonstrate the grafting of granular polyaniline on the CNT . The electrochemical polymerization route for the preparation of CNT/PANI nanocomposites showed that PANI nanofibers wrapped around the carbon nanotube . Electrochemical polymerization route is expensive and not suitable for mass production.…”
Section: Introductionmentioning
confidence: 99%
“…CNT/PANI nanocomposites prepared via in situ polymerization methods demonstrate the grafting of granular polyaniline on the CNT . The electrochemical polymerization route for the preparation of CNT/PANI nanocomposites showed that PANI nanofibers wrapped around the carbon nanotube . Electrochemical polymerization route is expensive and not suitable for mass production.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in our previous study concerning several parasubstituted arenediazonium salts [10], also in the case of NABDBF 4 À the reduction at the polypyrrole electrode occurs more easily (E p approx. +0.1 V) than at the other electrodes (E p approx.…”
Section: Electrochemical Reduction Of 4-[(4 0 -Nitrophenyl)azo] Benzementioning
confidence: 69%
“…The 4-[(4 0 -nitrophenyl)azo]benzenediazonium tetrafluoroborate (NABDBF 4 À ) was prepared by diazotisation of 4-amino-4 0 -nitroazobenzene with sodium nitrite in 40% fluoroboric acid solution as described in our previous studies [3,4].…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of grafted diazonium salt as adhesion promoter for the electropolymerisation of conducting polymers is well known [40][41][42][43]. Particularly, among the wide variety of monomers to generate conducting polymers, pyrrole is of particular interest mainly because of its relatively low oxidation potential (~ 0.8 V/SCE).…”
Section: Introductionmentioning
confidence: 99%